SLAVERY SYSTEM: UPAYA PENGHAPUSAN PERBUDAKAN MELALUI NABI MUHAMMAD SAW MASA AWAL ISLAM ABAD KE-7 M - Husna, Nurul Laelatul; Badrun, Badrun (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
In the past, slavery coult not be separated from the influence of history, culture, and traditions of societies in various part of the world that recognize slaves. There is an assumption, especially among Western orientalists that slavery is a result of Islamic culture. This article provides an in depth review and understanding of the relationship between slavery and Islam in reality. This literature study used an analytical approach by examining texts supported by four historical methods, namely heuristics, criticism, interpretation, and historiography. This study produced three finding. First, the slavery system in not the result of Islamic ijtihad but has developed universally in various parts of the world long before Islam emerged. Second, Islam has good treatment of slavery, especially in its concept of equality. Third, the abolition of slavery was been started during the time of the Prophet and people only need to continue the efforts. Keyword: Slavery system, Abollition efforts, Early Islam, Prophet Muhammad SAW